Design and fabrication of toolbox - Mohd Dzohairy, Mohammad Mohsan (2007)
Development of this toolbox is for store a workshop's tool or a light tool like screw driver and hammer at home. With the bigger size, this toolbox can store more tools inside it. Even though the size of this toolbox is big, but it is light because this toolbox is made from an aluminium metal. This toolbox make easy to person ~o bring it anywhere because the fIrst compartment can carryout from the toolbox and it has handle. Whole of this project is particular involves the toolbox. Diploma final year project will allocate the one semester to complete a project. This project also required the adequate student to finish a task given. The tasks division need to apply, for the entirely two part will be make that is a process to development of parts and assemble the toolbox.